Deformation analysis of existing tunnels with shearing and bending stiffness reduction at movement joints. (May 2022) - Liu, Xiang; Fang, Qian; Jiang, Annan; Li, Jianye
Highlights: Six deformation mechanisms of an existing tunnel are summarised. The analytical solution of existing tunnel's discontinuous deformation is proposed. Stiffness reductions at movement joints are considered using Dirac Delta function. The method is verified from centrifuge tests and compared with other methods. Characteristics of deformation mechanisms and influencing factors are discussed. Abstract: In urban areas, new tunnels are frequently constructed beneath existing tunnels. The common prediction of the deformation of existing tunnels depends on an elastic continuous assumption. The simple assumption neglects the discontinuous deformation of existing tunnels with movement joints. Relative rotation and dislocation at the movement joints significantly affect the deformation mechanism of existing tunnels. In this paper, six deformation mechanisms of an existing tunnel are summarised according to some case studies in Beijing. An analytical solution using the Dirac Delta function is proposed to study the responses of the existing tunnel with movement joints. The shearing and bending stiffness reduction at the movement joints are both separately considered instead of using the equivalent bending stiffness. The proposed method is verified from the data of centrifuge tests and compared with some reported methods. The characteristics of the six deformation mechanisms calculated by our method are studied. The deformation mechanisms have their own specific characteristics, depending on the relative location between movement joints and new tunnels. The parametric analyses indicate that the discontinuous deformation increases with the increased shearing stiffness reduction and bending stiffness reduction, whereas decreases with the increased Pasternak model's parameters. If the parameters are small enough to a certain extent, the effects will be insensitive.